Bone Health - Jacob Young; Jennifer Hillan (EDIS, 2012)
“When planning your family meals, you probably try to make sure your children get enough calcium and vitamin D, perhaps including a fresh cup of milk. Since milk is full of calcium, vitamin D, and other important nutrients, it’s one of the best foods for building strong bones. People who don’t get enough calcium or vitamin D are at risk for osteoporosis: weak bones that are more likely to fracture.” This 2-page Family Album Radio transcript was written by Jacob Young and Jennifer Hillanm and published by the UF Department of Family, Youth and Community Sciences, September 2012.